PENANAMAN KARAKTER DALAM PEMBELAJARAN MATEMATIKA DI KELAS VII SMP ISLAM AL-ISHLAH BUKITTINGGI - Muhammad Imran; Aniswita (KOLONI, 2022)
This research is motivated by the inculcation of character which is the school's vision, at Al-Ishlah Islamic Junior High School Bukittinggi. The school's vision reads, "Creating Religious, Character, Intellectual and Skilled People", and also based on initial observations, researchers see good character shown by students. One of the actions taken by Al-Ishlah Islamic Junior High School to realize the school's vision is to instill character in learning, including in learning mathematics. This study aims to describe the cultivation of character in learning mathematics in class VII SMP Islam Al-Ishlah Bukittinggi. This research is a qualitative descriptive research. This study uses 3 kinds of data collection techniques, namely, interviews, observation and documentation. The validity of the data in this study used source triangulation and method triangulation. The data analysis technique of this research is to combine the concepts of Miles and Huberman with Spradley and Yin. Based on the research results, character planting in mathematics learning goes through 3 stages, namely: character planting in learning planning, character planting in the process of implementing learning and character planting in learning evaluation. In planning learning mathematics, in the lesson plans there are elements of character planting on learning objectives and a focus on attitude values, then carried out in learning steps, starting from opening activities, core activities and closing. In the mathematics syllabus, the element of character building is seen in KI-1 and KI-2 and there are indicators of character strengthening education. There are 6 indicators that become the focus of character planting in mathematics learning, namely: religious, discipline, hard work, curiosity, confidence and responsibility. Character planting in the learning process is carried out, starting from the beginning to the end of the learning process, starting from the opening by praying, then when the teacher explains the material and gives assignments, the teacher instills discipline, hard work, curiosity, confidence and responsibility to the participants. educate. Planting character in learning evaluation is carried out at every meeting by assessing the attitudes of students in attitude assessment journals and by giving questions that contain elements of character. Keyword: Character, Character Cultivation, Mathematics Learning